Exploring the Feasibility and Effectiveness of Youth-Aging in Reality TV Programs Using Virtual Reality Technology - Ziming Wang (Studies in Social Science & Humanities, 2023)
This paper explores the feasibility and effectiveness of using virtual reality (VR) technology to attract young viewers to TV programs. The aging audience of TV programs is causing difficulties for the industry, and VR technology can create a new virtual space and a rich sensory experience to engage younger audiences. VR can also create new program forms, increase audience participation, and enhance the sense of belonging. From the perspective of program effect, VR can produce more modern programs, enhance entertainment value, and improve real-time performance. Studies show that the use of VR technology in TV programs attracts more young viewers, improves ratings, and increases user satisfaction. The paper concludes that the application of VR technology is crucial in the process of TV program youth and has great potential for future development. It can create a novel program experience, increase audience participation and satisfaction, attract more young viewers, expand the market space, and enhance the social influence of TV programs.